Hepatoprotective Effects of Panus giganteus (Berk.) Corner against Thioacetamide- (TAA-) Induced Liver Injury in Rats - Wong, Wei Lun; Abdulla, Mahmood Ameen; Chua, Kek Heng; Kuppusamy, Umah Rani; Tan, Yee Shin; Sabaratnam, Vikineswary (Hindawi, 2012)
Panus giganteus, a culinary and medicinal mushroom consumed by selected indigenous communities in Malaysia, is currently being considered for large scale cultivation. This study was undertaken to investigate the hepatoprotective effects of P. giganteus against thioacetamide- (TAA-) induced liver injury in Sprague-Dawley rats. The rats were injected intraperitoneally with TAA thrice weekly and were orally administered freeze-dried fruiting bodies of P. giganteus (0.5 or 1 g/kg) daily for two months, while control rats were given vehicle or P. giganteus only. After 60 days, rats administered with P. giganteus showed lower liver body weight ratio, restored levels of serum liver biomarkers and oxidative stress parameters comparable to treatment with the standard drug silymarin. Gross necropsy and histopathological examination further confirmed the hepatoprotective effects of P. giganteus. This is the first report on hepatoprotective effects of P. giganteus. The present study showed that P. giganteus was able to prevent or reduce the severity of TAA-induced liver injury.